Application of platelet-rich plasma in spinal surgery - Wang, Hengyi; Zhu, Jianshu; Xia, Yuanliang; Li, Yuehong; Fu, Changfeng (Frontiers in Endocrinology, 2023)
With the aging of the population and changes in lifestyle, the incidence of spine-related diseases is increasing, which has become a major global public health problem; this results in a huge economic burden on the family and society. Spinal diseases and complications can lead to loss of motor, sensory, and autonomic functions. Therefore, it is necessary to identify effective treatment strategies. Currently, the treatment of spine-related diseases includes conservative, surgical, and minimally invasive interventional therapies. However, these treatment methods have several drawbacks such as drug tolerance and dependence, adjacent spondylosis, secondary surgery, infection, nerve injury, dural rupture, nonunion, and pseudoarthrosis. Further, it is more challenging to promote the regeneration of the interstitial disc and restore its biomechanical properties. Therefore, clinicians urgently need to identify methods that can limit disease progression or cure diseases at the etiological level. Platelet-rich plasma (PRP), a platelet-rich form of plasma extracted from venous blood, is a blood-derived product. Alpha granules contain a large number of cytokines, such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), epidermal growth factor, platelet factor 4 (PF-4), insulin-like growth factor-1 (IGF-1), and transforming growth factor-β (TGF-β). These growth factors allow stem cell proliferation and angiogenesis, promote bone regeneration, improve the local microenvironment, and enhance tissue regeneration capacity and functional recovery. This review describes the application of PRP in the treatment of spine-related diseases and discusses the clinical application of PRP in spinal surgery.